Filipino students' adversity quotient and school connectedness - Payao, Concepcion; Balijon, Meshel; Ancho, Inero (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study determined the adversity quotient (AQ) and the school connectedness (SC) of education students in one of the state universities in Region VII, Philippines and establish if there is an influence between AQ and SC. Randomized sampling through fishbowl technique was employed in this study which were participated by one hundred (100) third year Education students from Bachelor of Elementary Education (BEED) and Bachelor of Secondary Education (BSED). There were two (2) major research tools used: AQ using student norm and self-made school connections checklist. The result revealed a significant relationship between overall AQ and SC of the respondents by computing Pearson Product Moment Correlation (Pearson r). However, the reach dimension of AQ showed no significant relationship between factors of SC. Lastly, AQ does not affect the respondents’ connectedness in school in factors like commitment to education and school environment. Hence, this study concluded that AQ is a predictor of SC.